PENGARUH BELANJA PEMERINTAH PUSAT UNTUK FUNGSI LINGKUNGAN HIDUP TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Wawan Hermawan (Quantitative Economics Journal, 2017)
Economic development is measured by economic growth. Improving the economy can improve the quality of life in society, so a lot of effort from the government to stimulate the economy to grow better. The positive growth of economy has an impact on the environmental quality of life such as degradation of quality of air, water and land. The government allocates some funds to maintain the quality of the environment by the central budget allocation for environmental functions. The purpose of this study is to measure the impact of the budget allocation for the function of the environment to economic growth. The model used to achieve the purpose of the study is the regression of total government spending to economic growth. To bridge from the expenditure function of the environment against government spending and economic growth model is used Growth Accounting Model. Results of regression calculations and simulations using Growth Accounting, shows expenditures for environmental function has the effect to increase the economic growth of 0.01% if no additional growth in the rest of expenditures for environmental functions by 10% ceteris paribus.